Development of Web-Based Interactive Media using genially in Food Technology Course of Culinary Arts Education Study Program - Mutiara, Erli; Sutanti, Siti; Dalimunthe, Dian Agustina; Sasmita, Rossy Luckita (Journal of Ecohumanism, 2024)
This research aims to: 1) Develop an interactive media using the Genially website in Food Technology course; 2) To gauge the students response towards the Genially media. It was conducted in Culinary Arts Education Study Program of State University of Medan. The research was carried out in April-June 2024. This was a research & development study using the ADDIE development model, consisting of Analysis, Design, Development, Implementation, Evaluation. The media was validated by 3 subject matter experts and 3 media experts, as well as 30 students as the users. The data collection technique was questionnaire. The data was analysed descriptively. The results show that the Genially media can be distributed and implemented in Food Technology course. The validation results from subject matter experts and media experts are in very good category with an average score of 94 percent. Students response towards the media is in very high category with a score of 4.94 out of 5. It can be concludeed that Genially-based media can be used in Food Technology course to improve students’ learning outcome in Culinary Arts Study Program.